Peran EGD Terhadap Kesadaran Pemotor Pada Trotoar dan Lajur Sepeda Di Kota Bandung - Destriana Prasetyo Wibowo; Aldrian Agusta (PT. Hasba Edukasi Mandiri, 2025)
This research focuses on the potential of Environmental Graphic Design (EGD) to enhance motorcycle riders' compliance with traffic regulations, particularly regarding the use of sidewalks and bike lanes in Bandung City. The rampant violation of traffic rules by motorcycle riders has posed a serious threat to the safety of other road users, such as pedestrians and cyclists. Therefore, this study aims to find innovative design solutions to change rider behavior and create a safer and more comfortable road environment. This study is driven by the urgent need for effective design strategies to educate and remind the public about the importance of obeying traffic rules. In other words, this research seeks to explore how environmental graphic design can be utilized as a persuasive visual communication tool to drive behavioral change. Through a qualitative approach, this study will in-depth analyze the effectiveness of various EGD elements in attracting attention, conveying clear messages, and shaping new awareness among motorcycle riders. The results of this research are expected to make a valuable contribution to the development of more humane urban design. The findings of this study can serve as a reference for local governments and urban planners in formulating policy and design-based solutions to address complex traffic problems in urban areas. This research is also expected to inspire further research in the field of environmental design and human behavior.